Distribution, abundance and some features of the ecology of large carnivores in Kazakhstan: analytical review: Казахский национальный университет имени аль-Фараби, Казахстан, Алматы; РГП «Институт зоологии» КН МОН РК, Казахстан, Алматы (Eurasian Journal of Ecology, 2018)
This article presents data on the distribution, abundance and lifestyle of large carnivorans living inthe territory of Kazakhstan, based on publications and collected new materials from the various regionsof the country.From large carnivores in the territory of the republic there are found representatives of the family ofCanidae (the wolf – Canis lupus), Ursidae (the brown bear – Ursus arctos, 2 subspecies), Mustelidae (thewolverine – Gulo gulo) and Felidae (the lynx – Lynx lynx, 3 subspecies, the caracal – Caracal caracal, thesnow leopard – Uncia uncia). Until the 1950s and 1970s there were also the red wolf (Cuon alpinus),tiger (Panthera tigris) and cheetah (Acinonyx jubatus). According to the analytical review, it can be seenthat the range, as well as the abundance of most of these species of large carnivores, are greatly reduced.Nowadays, there are almost no full-scale researches on the distribution and abundance of most largecarnivoran species. Moreover, since the data available so far are mostly obsolete or fragmentary, it isnecessary and relevant to continue research on the biology and ecology of lar Key words: large carnivorans, distribution, habitats, abundance, lifestyle